A new fossil green lacewing (Neuroptera: Chrysopidae) from the early Eocene Driftwood Canyon, Canada - Archibald, S. Bruce; Makarkin, Vladimir N. (Zootaxa, 2017)
Lithochrysa borealis sp. nov. (Neuroptera: Chrysopidae: Nothochrysinae) is described from the early Eocene locality at Driftwood Canyon (British Columbia, Canada). The forewing venation of the new species is similar to that of the late Eocene L. wickhami (Cockerell, 1914) from Florissant (Colorado, U.S.A.), but is distinguished from it by a slightly longer intramedian cell and distinctly longer branches of RP to CuA between the pseudocubitus and the posterior margin.